1998
DOI: 10.1103/physrevlett.81.874
|View full text |Cite
|
Sign up to set email alerts
|

Fano Resonances in Semiconductor Superlattices

Abstract: We report the first observation of Fano resonances in biased semiconductor superlattices: The excitonic Wannier-Stark ladder transitions show asymmetric absorption due to the coupling to the continua of lower transitions. In contrast to other known examples of Fano resonances, the Fano coupling can be continuously tuned in this system by changing the static field across the superlattice. The line shapes and their coupling dependence are in excellent agreement with theory. We also investigate the dephasing dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 18 publications
5
60
0
2
Order By: Relevance
“…[1][2][3][4] Extensive work has been done to investigate the specifics of the excitonic optical properties of quantum wells, 1,2 quantum wires, [3][4][5][6] quantum dots, [7][8][9][10] and superlattices. [11][12][13][14][15][16] The optical spectra of semiconductor structures can be modified dramatically by the application of external static electric and/or magnetic fields. For semiconductor quantum wells, the Franz-Keldysh ͑FK͒ effect occurs when an electric field polarized in the plane of the quantum wells is applied, while the quantum-confined Stark effect prevails for a field polarized in the growth direction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Extensive work has been done to investigate the specifics of the excitonic optical properties of quantum wells, 1,2 quantum wires, [3][4][5][6] quantum dots, [7][8][9][10] and superlattices. [11][12][13][14][15][16] The optical spectra of semiconductor structures can be modified dramatically by the application of external static electric and/or magnetic fields. For semiconductor quantum wells, the Franz-Keldysh ͑FK͒ effect occurs when an electric field polarized in the plane of the quantum wells is applied, while the quantum-confined Stark effect prevails for a field polarized in the growth direction.…”
Section: Introductionmentioning
confidence: 99%
“…FR was observed in a variety of atomic and molecular systems. Recently, this phenomenon has been reported in semiconductor quantum wells [2], in biased semiconductor superlattices (SSL's) [3], and in bulk GaAs in the presence of magnetic field [4,5] where discrete excitons couple to continua of the lower transitions through Coulomb interaction [6]. In addition to the frequency-domain experiments, transient four-wave mixing (FWM) in magneto-confined bulk semiconductors [5] and in SSL's [3] has demonstrated that the FR is a fundamental type of dephasing mechanism in irreversible quantum dynamical processes.…”
mentioning
confidence: 99%
“…3 (c), follows approximately the Fano coupling parameter γ [ Fig. 3 (b)], indicating that the DFR plays a role in intrinsic phase-breaking process as the usual FR does in biased SSL's [3,19].…”
mentioning
confidence: 99%
See 2 more Smart Citations